2019
DOI: 10.1186/s12995-019-0246-9
|View full text |Cite
|
Sign up to set email alerts
|

Does stigmatization moderate the association between intention and implementation of learned prevention-strategies at work after a depressive episode? – a cross-sectional pilot study

Abstract: BackgroundA depressive episode is a frequent reason for production loss due to long periods of absence at work. To maintain work ability after depression, affected employees need to implement learned coping strategies from interventions at work. Based on the theory of planned behavior, this paper examines how stigmatization relates to the implementation of the learned strategies at the workplace. Further, differences between employees with single or recurrent depressive episode were considered.MethodsData of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The initial search yielded 822 hits, with 698 after the removal of duplicates ( Figure 1 ). After title and abstract review, 41 full-text articles were assessed for eligibility, and 33 studies met the inclusion criteria and were retained in the final review [ 16 , 21 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. The majority of the studies utilized a noncontrolled timeseries or pre-post design, with follow-up periods ranging from 1 week to 6 months ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial search yielded 822 hits, with 698 after the removal of duplicates ( Figure 1 ). After title and abstract review, 41 full-text articles were assessed for eligibility, and 33 studies met the inclusion criteria and were retained in the final review [ 16 , 21 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. The majority of the studies utilized a noncontrolled timeseries or pre-post design, with follow-up periods ranging from 1 week to 6 months ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies found particular perceptions or beliefs that moderated the intention–behavior gap ( Table 1 and Table 2 c, and Figure 3 ) [ 56 , 57 ]. Specifically, Gaum and colleagues [ 56 ] found that lower anticipated stigma resulted in the increased implementation of depression prevention strategies in the workplace.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nielsen et al ( 45 ) have argued that stigma attached to mental health problems may even lead to dismissal when the employer anticipates low productivity after RTW. For employees, especially anticipated stigmatization can interfere with the RTW process ( 46 ).…”
Section: Discussionmentioning
confidence: 99%